Motivations and Efforts in English Language Teaching: Experiences of Secondary-level Teachers in Nepal - Panthee, Dinesh; Aryal, Bishnu Prasad (International Research Journal of Parroha, 2025)
Teachers’ professional choices are generally shaped by a complex interplay of extrinsic, intrinsic, and altruistic motivations. The purpose of the study was to explore the motivations and efforts that influence English language teachers in choosing teaching as their profession. This aimed to identify the reasons behind teachers’ career choices in English language teaching, to examine their professional growth and development as ELT practitioners, and to investigate their levels of job satisfaction within the profession. It was a narrative inquiry method that used in-depth interview methods to collect the data. The participants of the study were four secondary-level ELT teachers from four secondary schools in the Rupandehi district, Nepal. The thematic analysis method was used in the analysis of the data. The findings of this study revealed that English language teachers were motivated by a combination of intrinsic passion, social and familial influences, global aspirations, and ongoing professional development, which collectively shape their professional identity and practice. The study focused on the need to create supportive environments that nurture motivations and efforts for choosing English language teaching as a profession in Nepal.